The role of universities in the development of plurilingual repertoires: the voices of non-traditional adult students - Ambrósio, Susana
The purpose of this paper is to present a study on the non-traditional adult students’ (NTAS) perceptions concerning the role of university in the development of their plurilingual repertoires. Data were collected through biographical interviews with NTAS with fewer and more plurilingual experiences. The results show that NTAS with more plurilingual experiences are more aware of their plurilingual repertoire and acknowledge higher education as an opportunity to further develop it. It also appears that if university promotes a favourable environment for the development of plurilingual repertoires, there may be a change in NTAS’ perception regarding lifelong language learning.